(untitled) (Research, Society and Development, 2022)
The solution of environmental crimes, within the scope of legal proceedings processed by the Judiciary, often requires the need for intervention from various fields of knowledge, including environmental expertise. This type of expertise consists of a means of producing evidence capable of unraveling the extent of the environmental damage to the environment and, consequently, estimating the necessary repair, either in the form of indemnity or obligation to do so. In addition, the environmental expertise subsidizes the judge with specific knowledge that is beyond their academic training, even helping them to substantiate the judgment that will be handed down. Thus, taking into account that the 1988 Constitution, in the rule enshrined in art. 225, ensures that everyone has the right to an ecologically balanced environment, a good for common use by the people and essential to a healthy quality of life, imposing on the Public Power and the community the duty to defend and preserve it for the present and For future generations, combating environmental crimes is a duty of the State, and for that, environmental expertise represents a great ally in solving crimes that violate the environment (environmental good). That said, given its importance, this article aims to present how environmental expertise has contributed in the Judiciary Power to solve environmental crimes, especially in the Legal Amazon region. The methodological path to be followed is that of bibliographical and documental research, with consultation of books, periodicals, articles, dissertations and normative diplomas related to the subject.